2023
DOI: 10.3390/pathogens12081062
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Listeria innocua Isolates Recovered from Cattle Farms, Beef Abattoirs, and Retail Outlets in Gauteng Province, South Africa

James Gana,
Nomakorinte Gcebe,
Rian Ewald Pierneef
et al.

Abstract: Whole-genome sequencing (WGS) was used for the genomic characterization of one hundred and ten strains of Listeria innocua (L. innocua) isolated from twenty-three cattle farms, eight beef abattoirs, and forty-eight retail outlets in Gauteng province, South Africa. In silico multilocus sequence typing (MLST) was used to identify the isolates’ sequence types (STs). BLAST-based analyses were used to identify antimicrobial and virulence genes. The study also linked the detection of the genes to the origin (industr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 71 publications
1
7
0
Order By: Relevance
“…In our study, L. innocua was detected with a higher farm prevalence than L. monocytogenes (11.3% versus 3.4%) and from each sample type (faeces, feeds, silage, and drinking water) collected from cattle farms in our study. These findings agree with published reports that L. innocua has a broader distribution on cattle farms elsewhere (Gradovska et al 2023 ; Gana et al 2023 ). However, considering the organism is viewed as a non-pathogen, the risk of causing livestock and human listeriosis is minimal.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, L. innocua was detected with a higher farm prevalence than L. monocytogenes (11.3% versus 3.4%) and from each sample type (faeces, feeds, silage, and drinking water) collected from cattle farms in our study. These findings agree with published reports that L. innocua has a broader distribution on cattle farms elsewhere (Gradovska et al 2023 ; Gana et al 2023 ). However, considering the organism is viewed as a non-pathogen, the risk of causing livestock and human listeriosis is minimal.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, there is a potential for tetracycline-resistant L. innocua strains to enter the human food chain. It is relevant to mention that the prevalence of phenotypic tetracycline resistance exhibited by the same isolates of L. innocua using the disc diffusion method was 36.8% [37]. Interestingly, this phenotypic resistance correlates well with the putative resistance to tetracycline due to both the tet(M) and tet(S) genes, suggesting that the genes may have been partly responsible for the resistance detected.…”
Section: Discussionmentioning
confidence: 86%
“…This is attributed to the existing Fertilizers, Farm, and Agricultural and Stock Remedy Act (Act 36, 1947), which legalizes the use of certain antimicrobial agents, such as sulphonamides and trimethoprim, to be purchased over-the-counter, and they are used for treatment and as growth promoters [70]. Interestingly, the phenotypic resistance exhibited to tetracycline (36.8%) determined by Gana [37] correlates well with the putative resistance to tetracycline due to both tet(M) and tet(S) genes based on WGS on the same isolates, suggesting that the genes may have been partly responsible for the resistance detected. Other studies have similarly reported the correlation between phenotypic resistance and the carriage of corresponding encoding resistance genes [65,71,72].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…obtained from beef processing environments [40] and the red meat and poultry value chain [55]. Most recently, Gana et al [56] used WGS to characterize L. innocua isolates from cattle farms, abattoirs, and retail outlets. To date, there is a dearth of comprehensive information on the WGS analysis of L. monocytogenes circulating in the beef production chain's three levels (production, processing, and retailing) in Gauteng province, South Africa.…”
Section: Introductionmentioning
confidence: 99%